Association of vitamin D3 deficiency with autoimmun hypothyroidism in Southern Iraqi patients: A regional study from Thi-Qar Province - Tkhadum, Zaeinab; Mousa, Hind M (Edelweiss Applied Science and Technology, 2025)
Autoimmune hypothyroidism is immune-mediated destruction of thyroid tissue. Emerging evidence highlights D3 immunomodulatory role in autoimmune diseases, although its association with thyroid autoimmunity in Iraq remains understudied. Objective: This study aimed to evaluate vitamin D3 levels in Hashimoto’s patients compared to controls and assess the correlations between vitamin D3, thyrotropin hormone (TSH), and anti-thyroid peroxidase (TPO-Ab). A case-control study at Al-Refai Hospital and Al-Haboubi Teaching Hospital/ Iraq comprised 50 Hashimoto’s patients and 50 age- and sex-matched healthy controls. TSH, TPO-Ab, and 25-hydroxyvitamin D3 were assessed using fluorescence and chemiluminescence assays. Patients exhibited significantly lower vitamin D3 levels (21.27 ± 7.6 ng/mL) compared to controls (35.45 ± 11.8 ng/mL; p<0.01). Patients had elevated TSH (10.25 ± 3.7 vs. 1.89 ± 0.81 μIU/mL) and TPO-Ab (58.6 ± 17.4 vs. 6.2 ± 5.3 IU/mL) (p<0.01). Weak, non-significant negative correlations were found between vitamin D3 and TSH (r = -0.04) and TPO-Ab (r = -0.099). ROC analysis confirmed that TSH and TPO-Ab were highly sensitive biomarkers for Hashimoto. Vitamin D3 deficiency is strongly associated with autoimmune hypothyroidism in southern Iraqi patients. These findings suggest potential therapeutic benefits of vitamin D3 supplementation in managing the condition, warranting further clinical trials.